Histopathological findings of infections caused by canine distemper virus, Trypanosoma cruzi, and other parasites in two free-ranging White-nosed Coatis Nasua narica (Carnivora: Procyonidae) from Costa Rica - Rojas Jiménez, Jorge (2021)
Canine distemper virus (CDV) causes systemic infections and immunosuppression in carnivores, which subsequently makes animals highly susceptible to opportunistic infections. Although Trypanosoma cruzi infects procyonids, chagasic myocarditis in Coatis has not been reported in Central America. The aim of this study was to report the histopathological findings caused by canine distemper virus, T. cruzi, and other parasites in two free-ranging White-nosed Coatis Nasua narica found dead in a national park on the Pacific coast of Costa Rica. Heart, lung, tongue, liver, brain and spleen samples were subjected to macroscopic and microscopic examination. A mononuclear meningoencephalitis associated with intra-nuclear eosinophilic inclusion bodies consistent with canine distemper virus was observed in nervous tissue. Myocarditis and associated nests of amastigotes of T. cruzi were observed during microscopic examination in cardiac tissue, and in muscle from the tongue of both animals. Molecular analysis confirmed T. cruzi in formalin-fixed paraffin embedded cardiac tissues. The myocardial damage caused by the opportunistic infection due to T. cruzi in these individuals could be the result of a severe compromised immunological status associated to the CDV infection, and subsequent opportunistic polyparasitism described herein. To the authors knowledge this is the first report of chagasic myocarditis in free-ranging coatis from Central America.